The impact of COVID-19 on GCC equity and debt markets: Evidence from TVP-VAR estimation - Syed, Ali Murad (Frontiers in Applied Mathematics and Statistics, 2022)
COVID-19 impacted the financial markets of the world, and it has rapidly evolved into a global pandemic that has strongly impacted all financial markets, including GCC region. Since the outbreak is unprecedented, there is a need to analyze the effects of the disease on the volatility spillovers between equity and bond markets. We empirically investigate the impact of the COVID-19 pandemic on the financial equity and debt markets in the Gulf Cooperation Council (GCC) region. We used the dynamic connectedness TVP-VAR approach to measuring risk transmission in the GCC markets. This paper investigated the time-varying behavior of GCC equity, conventional and Islamic debt markets using data from 1st January 2019 to 30th August 2021. The results were also validated by doing DCC-GARCH analysis to check the shock and spillovers among the GCC markets. We found the persistent shock transmitter roles of the equity markets to the bond and sukuk markets in the GCC region and the total dynamic connectedness is increased during the first wave of the COVID-19 pandemic. Overall, significant level of interconnectedness exists within the GCC markets.